From the Outside Looking In : 10 Working Artists. - USIS/AUA, United States Information Service, Chiang Mai (Chiang Mai : United States Information Service, 1989)
Boonma, Montian ; Chaiyakut, Pongdej ; Chandratita, Chaiyot ; Javanalikikorn, Kade ; Nakbanlang, Bannarak ; Osborne, J.R.S. ; Pungkasamesomboon, Thaiwijit ; Ribbarp, Niclas ; Srivichainan, Kamol ; Yukanthrapornpong, Tongchai
From the Outside Looking In : 10 Working Artists, USIS/AUA, United States Information Service, Chiang Mai, 10-22 february 1989
boek